Furthering caring through nursing education - D van der Wal (Curationis, 1999)
The nursing students’ main quest is for self actualization by attributing meaning to life through caring. To assist student nurses in this quest, the nurse educator needs to plan educational interventions according to an anthropological model that posits care and caring as innate human attributes. Further, the structural essence of what professional nursing caring entails should also be posited as a point of departure for curriculum planning. The author proposes such models. The main implications include that the nursing curriculum must increasingly attend to the emotional needs of nursing students. Curricular content and teaching strategies toward this goal are suggested.